Teleautonomous Control on Rescue Robot Prototype - Handy Wicaksono; Handry Khoswanto; Son Kuswadi (Universitas Ahmad Dahlan, 2012)
Robot application in disaster area can help responder team to save victims. In order to finish task, robot must have flexible movement mechanism so it can pass through uncluttered area. Passive linkage can be used on robot chassis so it can give robot flexibility. On physical experiments, robot is succeeded to move through gravels and 5 cm obstacle. Rescue robot also has specialized control needs. Robot must able to be controlled remotely. It also must have ability to move autonomously. Teleautonomous control method is combination between those methods. It can be concluded from experiments that on teleoperation mode, operator must get used to see environment through robot’s camera. While on autonomous mode, robot is succeeded to avoid obstacle and search target based on sensor reading and controller program. On teleautonomous mode, robot can change control mode by using bluetooth communication for data transfer, so robot control will be more flexible.